Analyzing defined contribution pension reform in Korea using a general equilibrium model - Seung-Ryong Shin (KDI Journal of Economic Policy, 2024)
Korea's National Pension Fund (NPF) is projected to be in deficit by the 2040s and exhausted by the 2050s. Increasing contribution rates may be unaffordable, prompting consideration of structural reforms, particularly shifting from a defined benefit (DB) to a defined contribution (DC) system. The DC system links benefits to contributions and investment returns, ensuring financial stability but raising concerns about income adequacy and redistribution. This study uses an overlapping generations model with heterogeneous agents to assess these reforms. By 2070, demographic changes will make the DB system unsustainable without substantial government subsidies, adversely affecting taxes, income, and savings. Conversely, the DC system would remain balanced without subsidies, resulting in lower interest rates, higher wages, and better economic output. The model shows that the DB system would require an annual subsidy of 11.3% of GDP at a 9% contribution rate by 2070, while the DC system would be self-sufficient. Even with lower returns, the DC system could be more efficient and equitable with partial subsidies, improving economic outcomes and reducing inequality.
Keywords: H55; J11; E60; 330; Defined Benefit; Defined Contribution; Pay-as-you-go; Public Pension; General Equilibrium; OLG; Aging